The Effects of Supplementation with Omega-3 Polyunsaturated Fatty Acids on Cardiac Rhythm: Anti-Arrhythmic, Pro-Arrhythmic, Both or Neither? It Depends… - Rauch, Bernhard; Senges, Jochen (Frontiers in Physiology, 2012)
Supplementation of omega-3 fatty acids (Ω-3) has been associated with a decreased cardiovascular risk, thereby concentrating attention on a potentially preventive effect regarding tachyarrhythmias and sudden cardiac death. However, recent randomized controlled trials challenge the efficacy of the additional application of Ω-3 and its anti-arrhythmic effect under certain clinical conditions. The present paper reflects the results of earlier and recent clinical studies with respect to the individual background conditions that may determine the clinical outcome of Ω-3 supplementation and thereby explain apparently conflicting clinical results. It is concluded that the efficacy of Ω-3 supplementation to prevent cardiac arrhythmias strongly depends on the underlying clinical and pharmacological conditions, a hypothesis that also is supported by data from experimental animal studies and by molecular interactions of Ω-3 at the cellular level.